Kinetic evaluation of the solvolysis of isobutyl chloro- and chlorothioformate esters - D’Souza, Malcolm J (Beilstein-Institut, 2011)
The specific rates of solvolysis of isobutyl chloroformate (1) are reported at 40.0 °C and those for isobutyl chlorothioformate (2) are reported at 25.0 °C, in a variety of pure and binary aqueous organic mixtures with wide ranging nucleophilicity and ionizing power. For 1, we also report the first-order rate constants determined at different temperatures in pure ethanol (EtOH), methanol (MeOH), 80% EtOH, and in both 97% and 70% 2,2,2-trifluoroethanol (TFE). The enthalpy (ΔH(≠)) and entropy (ΔS(≠)) of activation values obtained from Arrhenius plots for 1 in these five solvents are reported. The specific rates of solvolysis were analyzed using the extended Grunwald–Winstein equation. Results obtained from correlation analysis using this linear free energy relationship (LFER) reinforce our previous suggestion that side-by-side addition–elimination and ionization mechanisms operate, and the relative importance is dependent on the type of chloro- or chlorothioformate substrate and the solvent.